AERODYNAMIC CHARACTERISTIC AND AIRPLANE STABILITY AT THE PLERIMENARY DESIGN STAGE - Meiyanto Eko Sulistyo; Muhammad Ikyu Arqie Ramadhan; Ardya Paradipta Sylvano Inderawan (Universitas Sebelas Maret (UNS), 2020)
Preliminary Design is the second stage in aircraft design after knowing the needs and specifications at the Conceptual Design stage. This Preliminary Design includes the conceptual design evaluation of aircraft performance in several fields, such as aerodynamics, engine power, and aircraft structure. This Job Training Report illustrates how is taken to conduct aerodynamic and aircraft stability analysis at the plerimenary design stage using NASA's open source software, Open Vehicle Simulation Program (OpenVsp). The aircraft model is simulated until aerodynamic and stability data are obtained which later can be processed for aircraft control design.